Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1002/anie.201904329
|View full text |Cite
|
Sign up to set email alerts
|

Bowl Inversion in an Exo‐type Supramolecule in the Solid State

Abstract: Bowl inversion is aunique property of buckybowls. The polarity and assembly configuration of buckybowls are reversed after bowl inversion. So far,this unique phenomenon has been studied in solution and on surface,b ut not in solid state due to spatial constraint. Now as eries of exo-type supramolecular assemblies of trithiasumanene and nanographene are investigated. Tuning the electron density of the nanogaphene component was found to directly affect the binding constant of the complex. Reversible bowl inversi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 80 publications
0
14
0
Order By: Relevance
“…Density functional theory (DFT) calculation revealed that the two conformers (P bay -1 and M bay -1) locate at the same level of free energy because of its C 2 -symmetry, and the reversion barrier of the helical bay region is 4.4 kcal/mol (Figure 1d), which is comparable with that of carbo [4]helicene (∼4.0 kcal/ mol), 33,34 indicating a rapid vibration process at ambient conditions. 35 The nitrogen atoms are both surrounded by one octagonal ring and two pentagonal rings with the sum of three internal angles (α + β + γ) in a range of 356.6−360°, depending on the vibration state of the whole molecule, which can be represented by the torsion angle of the bay region (Figure 1d,e).…”
Section: ■ Results and Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Density functional theory (DFT) calculation revealed that the two conformers (P bay -1 and M bay -1) locate at the same level of free energy because of its C 2 -symmetry, and the reversion barrier of the helical bay region is 4.4 kcal/mol (Figure 1d), which is comparable with that of carbo [4]helicene (∼4.0 kcal/ mol), 33,34 indicating a rapid vibration process at ambient conditions. 35 The nitrogen atoms are both surrounded by one octagonal ring and two pentagonal rings with the sum of three internal angles (α + β + γ) in a range of 356.6−360°, depending on the vibration state of the whole molecule, which can be represented by the torsion angle of the bay region (Figure 1d,e).…”
Section: ■ Results and Discussionmentioning
confidence: 96%
“…In conclusion, we have developed a feasible protocol involving octagonal Scholl-type cyclization and C−H arylation to simultaneously incorporate two nitrogen atoms into the octagonal ring of curved NGs. The resulting [1,4]diazocineembedded NGs revealed concave−convex cooperatively dynamic 5−5−8−5−5-membered ring skeletons and electron-rich characteristics. We have also demonstrated that the helical π-extension serves as an efficient method to modulate the molecular vibration of curved NGs as well as to control the dynamic chirality of the distal helical bay region.…”
Section: ■ Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bowl-shaped nanocarbons are a segment of curved carbon nanomaterials that include fullerenes, carbon nano-onions, and the cap of carbon nanotubes. As a result of their asymmetrical π-conjugated systems, bowls exhibit intriguing properties such as chirality, dynamic bowl inversion, ferroelectricity, and supramolecular recognition. The key to achieving the bowl shape is the incorporation of pentagons into the carbon skeleton. , Structurally, the pentagons are located at the inner core of the carbon skeleton, as in the case of corannulene, which is different from the honeycomb network of graphene . Alternatively, the construction of pentagons at the periphery of the carbon backbone can result in a bowl-shaped structure without the destruction of graphenic networks. , For example, the bowl-shaped molecule, sumanene, , is composed of a triphenylene core and three pentagons at the periphery of the triphenylene (Figure ).…”
mentioning
confidence: 99%
“…The structure of 2r was unambiguously confirmed by X-ray crystallographic analysis (Figure c). Sumanene, a C 3 v -symmetric buckybowl resembling a basic fragment of C 60 (Figure d), has received significant interest not only for its unique geodesic structure but also for its properties. , Various heteroatoms have been used to replace the carbons of sumanene to tune the structures and intrinsic properties. , The synthesis of heterosumanene poses a great challenge to chemists. , Recently, we reported the synthesis of sulfur- and selenium-doped sumanenes; however, tellurium-containing sumanene could be obtained under similar conditions . In 2016, Shao et al reported the first ultrasound-assisted synthesis of tritellurasumanene with hexa-alkoxyl groups on its periphery through the lithiation of hexa-alkoxy-substituted triphenylene, followed by treatment with tellurium powder; however, this method could not afford pristine tritellurasumanene.…”
mentioning
confidence: 99%